2019
DOI: 10.1016/j.msec.2019.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterisation of multi vs. uni-directional carbon fiber frameworks for dental implant applications

Abstract: The aim of the present study was to investigate the mechanical characteristics of dental implant frameworks made of unidirectional carbon fiber composite (UF) and to compare them with those provided by multidirectional carbon fiber composite (IF). Methods: 8 different UF samples were used. The samples were initially evaluated by optical microscope and SEM then non-destructive and destructive mechanical tests were performed on 4 samples in order to evaluate dynamic, static elastic modulus, wettability and ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
1
15
0
5
Order By: Relevance
“…The main differences between the results were the used raw material, as Costa 62 used a pre-impregnated carbon fiber with PPS, besides the use of unidirectional fibers aligned in the loading direction provides optimum strength. This research comprised a woven fabric that limits the fibers aligned in loading direction by 50%, in addition, the woven generates crimp regions which induces failure by buckling in the compression side 61,63 . This type of failure was reported in the previous section that comprises the misaligned fiber due to the waviness generated by woven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main differences between the results were the used raw material, as Costa 62 used a pre-impregnated carbon fiber with PPS, besides the use of unidirectional fibers aligned in the loading direction provides optimum strength. This research comprised a woven fabric that limits the fibers aligned in loading direction by 50%, in addition, the woven generates crimp regions which induces failure by buckling in the compression side 61,63 . This type of failure was reported in the previous section that comprises the misaligned fiber due to the waviness generated by woven.…”
Section: Discussionmentioning
confidence: 99%
“…The use of infrastructures in composites has recently been explored due to the advantages of having some advantages over metallic alloys, such as high flexural strength, high modulus of elasticity, low specific weight, allowing chemical adhesion of resins on the infrastructure and lower production cost 17,26,27,63,73 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast with metal alloy, CFRC is an anisotropic and non-homogeneous material, due to the fact that it is created by superimposing layers of carbon fibers embedded in a polymer matrix. For this reason, the manufacturing technique strongly affects the final characteristics of the prostheses [53]. A preliminary in vitro study on carbon fiber frameworks for dental implant applications [7] also reported that intact and fragmented carbon fiber samples showed optimal biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible weavability of carbon fiber also facilitate the combination design and fabrication of CFRP laminates with diverse ply orientations and layers, which would substantially affect the static and dynamic deformation behaviors and further regulate the mechanical properties. Considering the extensively potential applications of CFRP in the fields involving aviation, automobile, architecture and biomedical engineering fields, etc., 2–4 which would be confronted with various load types, including quasi static and dynamic loads, the sensibility of multi‐layer CFRP laminates to strain rate need to be taken into account 5,6 …”
Section: Introductionmentioning
confidence: 99%